Microbiological contamination of drinking water sources in tourist accommodations in South Luangwa National Park, Zambia - Albanus, Celina; Heggie, Travis; Kattner, Simone; Küpper, Thomas (Health Promotion & Physical Activity, 2022)
Background: Water quality for tourists visiting South Luangwa National Park and other less developed regions is of the utmost importance in order to avoid gastrointestinal infections; one of the most common diseases among tourists. It is also important to the health of the local tourist accommodations and the local tourist economy. Methods: Water quality samples assessing microbiological contamination were taken from the borehole and point of use in 14 tourist lodges and camps. Turbidity was assessed optically with a DelAlgua turbidity tube. For microbiological analysis, samples were incubated in the DelAgua Dual Incubator at 37°C and 44°C. Thermotolerant Escherichia coli (E. coli) was used as the indicator bacterium for fecal pollution. Water samples were classified based of risk levels for pollution determined by the World Health Organization (WHO). Results: Fifty percent of borehole samples showed no contamination. Two were found to be at high risk and the others ranged between low and intermediate risk. At the point of use, 80% of the samples were clean and compliant with WHO guidelines. Water contamination generally improved from the borehole to point of use. Turbidity at borehole samples were clear in 75% of possible samples. At the point of use, turbidity was clear in 81% of samples. Conclusion: This study establishes the first baseline water quality data for tourist facilities at South Luangwa National Park in Zambia. While water quality at most sites is clean for human use, a regular monitoring system accompanied by maintenance is recommended.